The Implementation of PSAK 106 on Profit-Sharing Recognition in Musyarakah Financing: A Case Study at Bank BJB Syariah - Toto Sugihyanto; Eko Sudarmanto; Ilza Febrina; Mohamad Ridwan; Isa Amsyari; Guruh Marhaenis Handoko Putro (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Musyarakah financing has experienced significant growth in Indonesian Islamic banking; however, the implementation of PSAK 106 in profit-sharing recognition remains inconsistent. Fixed profit-sharing practices that do not reflect actual business income may reduce transparency and sharia compliance. Objective: This study examines the implementation of PSAK 106 in recognizing profit-sharing for Musyarakah financing at Bank BJB Syariah. Methods: A qualitative case study and phenomenological approach were employed. Data were collected through in-depth interviews with three financing analysts and two Musyarakah customers, supported by financial document analysis from 2016–2020. Data were analyzed by comparing PSAK 106 requirements with actual banking practices, with validation conducted through member checking and source triangulation. Results: The findings reveal that Musyarakah profit-sharing recognition at Bank BJB Syariah has not been fully aligned with PSAK 106. The bank applies fixed monthly profit-sharing payments, whereas PSAK 106 requires recognition based on actual realized business income. The main discrepancy occurs in operating income recognition, where fixed percentages replace income-based calculations. Conclusion: Improving compliance with PSAK 106 is necessary to strengthen transparency, fairness, and accountability in Musyarakah financing practices within Islamic banking.